Analysis of Severity Level Types and Trends in Road Accident Cases at Johor Inter State Road Using Analythical Hierarchy Process (AHP) And Geographical Information System - Saifullizan, M.B; Nur , A. F. M. F; Nazirah, M.A; Anuar, M.S (International Journal of Integrated Engineering, 2022)
Road traffic accidents are usually happened and keep increasing year by year in Malaysia. It will give a adverse impact at the road also to the road user. There are several causes that contribute to the accident such as faulty vehicle, uneven roads, driver behavior and many more. So, with all these causes, it might be the reason why the road accidents keep on increasing. The purpose of this case study is to determine the highest road accident ranking based on the types of injuries at the state road, Johor. Another purpose is to identify the current traffic accident trends. Secondary data collected from Balai Polis Trafik, Batu Pahat are used to get an accident data and the Analythical Hierarchy Process (AHP) will be proceed to find the road accident ranking based on the types of injuries. The case study used the five years road accident data as from 2016 until October 2020 . Geoda as GIS application is used to insert the data about the road accident trends. The highest road accident ranking based on the types of injuries and the road accident trends were obtained and achieved all the objective of this case study. The hierarchy structure has founded highest ranking by types of injuries, which is the highest is Wreckage injuries that has the consistency ratio 2.92 which is the highest then the other value. The fatal injury has the second highest value which is 1.31, the minor is 0.88 and the lowest value is in the serious injuries which is 0.70 in consistency Ratio. In conclusion, by using the AHP it is more easy to find the rangking at any of problem issues and by using this method it can use primarily used to weigh the parameters and pick and rate the alternatives that have been chosen.Besides that, it will be useful as a reference to any party in the future for the road traffic management.